2017
DOI: 10.1111/trf.14311
|View full text |Cite|
|
Sign up to set email alerts
|

Metastatic spine tumor surgery: does perioperative blood transfusion influence postoperative complications?

Abstract: This study adds evidence to the literature implicating ABT to be influential on postoperative complications and infections in patients undergoing MSTS. Appropriate blood management measures should, therefore, be given a crucial place in the care of these patients so as to reduce any putative effect of blood transfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…In a single center study, the odds ratio of developing postoperative complications was 2.27 times higher in those who received a transfusion than in those who did not, with an increase in odds ratio of 1.24 per unit transfused (53). Transfusion is not associated with increased overall survival or disease-free survival (54). One method for decreasing transfusion rate is intraoperative cell salvage (IOCS) with a leukocyte depletion filter to remove malignant cells (55).…”
Section: Complicationsmentioning
confidence: 99%
“…In a single center study, the odds ratio of developing postoperative complications was 2.27 times higher in those who received a transfusion than in those who did not, with an increase in odds ratio of 1.24 per unit transfused (53). Transfusion is not associated with increased overall survival or disease-free survival (54). One method for decreasing transfusion rate is intraoperative cell salvage (IOCS) with a leukocyte depletion filter to remove malignant cells (55).…”
Section: Complicationsmentioning
confidence: 99%
“…17 A retrospective analysis by Zaw et al demonstrated that patients undergoing oncological spine surgery were at a twofold risk for overall perioperative complications when receiving ABTs. 18 Prospectively defining patients who are at risk for receiving ABTs can therefore help to enhance intraand perioperative management, including fluids, antibiotics, and coagulation, and improve the collaborative efforts of surgeons and anesthesiologists. We found that among patients with spinal metastases, those with myeloma presented with a significantly increased intraoperative blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…11 We acknowledge that this is applicable to MSTS patients as extended hospital stay reflects longer recovery from complex spinal procedures and accounts for occurrence of postoperative complications. 6,15 Similarly, Zaw et al 16 highlighted that operative parameters such as EBL and length of surgery may considerably influence the risk of postoperative complications after MSTS. Therefore, SMII may be considered as an indirect predictor of the risk of postoperative complications such as urinary tract infections, pneumonia, or deep vein thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 In addition, this index would assist in proper resource management and allocation in terms of anesthetic support, blood product management, and pre-booking of intensive care units. 16,25 Limitations The retrospective review of patient data for this study could potentially introduce selection and information bias. A prospective study may be needed to further validate our study findings.…”
Section: Discussionmentioning
confidence: 99%